Pengaruh Financial Leverage dan Operating Leverage terhadap Kinerja Keuangan Perusahaan Manufaktur di Bursa Efek Indonesia - Anthony Holly; Robert Jao; Ana Mardiana; Geraldy Frederick Dayoh (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2025)
This research aims to investigate the effect of financial leverage and operating leverage on financial performance. The population used in this research is financial data from the manufacturing sector listed on the Indonesia Stock Exchange (BEI) with a research period of 2021-2023. This research uses secondary data. Sample selection was carried out using a purposive sampling method to obtain a total sample of 13 companies over 3 years. The data analysis method used is linear regression analysis.The research results show that financial leverage has a positive and significant effect on financial performance, operating leverage has a positive and significant effect on financial performance. The implication of this research is that for investors, the results of this research can contribute to investors as a source to see the development of company performance in the capital market and can be used as material for consideration in making investment decisions in the future. And for companies, the results of this research can be used as consideration in improving company performance to manage company reports better.